2008
DOI: 10.1537/ase.070723
|View full text |Cite
|
Sign up to set email alerts
|

Root and canal morphology of human permanent teeth in a Sri Lankan and Japanese population

Abstract: The main purpose of this study was to investigate the root and canal morphology of Sri Lankan and Japanese permanent dentition. Two thousand Sri Lankan and 976 Japanese permanent teeth were examined. The number of roots in premolars and molars and the prevalence of C-shaped (gutter shaped) roots in mandibular second molars were recorded. Root canal morphology was studied using a clearing technique. The examination of root canal systems of the teeth was based on Vertucci's classification. A higher prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 44 publications
6
58
0
1
Order By: Relevance
“…In this study, we found that the type I have a higher percentage both in right and left mandibular second molars. Other than that, we found types 3-2 (2.5%) for mesial roots on right mandibular first molars, which was also found in studies by Peiriz et al and Mukhaimer et al Gulabivala et al [10] Sert et al [11] Ahmed et al [12] Rwenyonyi et al [13] Peiris [14] Subha et al [15] Caucasian …”
Section: Methodssupporting
confidence: 86%
“…In this study, we found that the type I have a higher percentage both in right and left mandibular second molars. Other than that, we found types 3-2 (2.5%) for mesial roots on right mandibular first molars, which was also found in studies by Peiriz et al and Mukhaimer et al Gulabivala et al [10] Sert et al [11] Ahmed et al [12] Rwenyonyi et al [13] Peiris [14] Subha et al [15] Caucasian …”
Section: Methodssupporting
confidence: 86%
“…, Vertucci , Velmurugan et al . , Peiris ). Clearly, in terms of clinical management of teeth undergoing root canal treatment, it is critical to define the number of roots, and not just canals, as this will have implications in terms of access cavity preparation, mechanical instrumentation and root canal filling procedures (Ahmed & Cheung ).…”
Section: Justification For a New Classification Systemmentioning
confidence: 99%
“…1g). Since then, this approach has become a standard method in endodontic research, and numerous reports [24][25][26][27][28][29][30][31][32][33][34] have been published that elucidate root canal systems using this so-called "clearing technique" (Fig. 1h).…”
Section: Traditional Methods Of Analyzing Internal Tooth Structuresmentioning
confidence: 99%